Komunikasi Interpersonal Guru Dengan Motivasi Belajar Siswa di MTS Teladan Ghupy - Fadhillah, Intan; Syafrizaldi, Syafrizaldi; Suharyanto, Agung; Hidayat, Taufik Wal; Riadi, Selamat (Universitas Medan Area, 2024)
This research aims to examine the relationship between Interpersonal Communication of Teachers and Students' Learning Motivation at Teladan Ghupy Middle School. The sample for this study consisted of 98 first-grade students. Learning motivation was measured based on characteristics such as diligence in facing tasks, perseverance in overcoming difficulties, showing interest in various problems, preferring to work independently, quickly getting bored with repetitive tasks, being able to maintain opinions, and not easily letting go of what is believed. Interpersonal communication in this study was measured based on Interpersonal Communication Aspects, including Openness, Empathy, Supportive Attitude, Positive Attitude, and Equality. The results of the analysis using the product moment correlation showed a positive relationship between interpersonal communication and learning motivation. This is evidenced by the correlation coefficient rxy = 0.890, with a significant value of p = 0.007 0.05. The coefficient of determination (r2) = 0.791, indicating that interpersonal communication contributes to learning motivation by 79.10%.